2019
DOI: 10.3390/nano9121646
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Investigation of CO2/CH4 Competitive Adsorption and Confinement in Realistic Shale Kerogen

Abstract: The adsorption behavior and the mechanism of a CO2/CH4 mixture in shale organic matter play significant roles to predict the carbon dioxide sequestration with enhanced gas recovery (CS-EGR) in shale reservoirs. In the present work, the adsorption performance and the mechanism of a CO2/CH4 binary mixture in realistic shale kerogen were explored by employing grand canonical Monte Carlo (GCMC) and molecular dynamics (MD) simulations. Specifically, the effects of shale organic type and maturity, temperature, press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…The rate at which the ultimate recovery can be reached, however, was determined by the connectivity of reservoir pores and the extent of the induced hydraulic fractures. The adsorption results of CH 4 –CO 2 presented in this study shared a similar trend to some others reported in the literature. ,,,, …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The rate at which the ultimate recovery can be reached, however, was determined by the connectivity of reservoir pores and the extent of the induced hydraulic fractures. The adsorption results of CH 4 –CO 2 presented in this study shared a similar trend to some others reported in the literature. ,,,, …”
Section: Resultssupporting
confidence: 91%
“…The results also showed that in the case of the CO 2 /CH 4 binary mixture, increasing the pressure resulted in a slight increase in carbon dioxide adsorption and a slight decrease in methane adsorption. They also examined the impact of thermal maturity on adsorption; the simulation results showed that a mature type II kerogen had a larger adsorption capacity than other type II kerogen molecules …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in-depth adsorption mechanism and confinement effect in realistic kerogen nanopores are still not fully understood. Based on our previous molecular studies on competitive adsorption of CO 2 /CH 4 in kaolinite clay and graphene slit-like nanopores in shale reservoirs, ,, we focused on the molecular investigation of gas adsorption mechanism and confinement effect in realistic kerogen nanopores in the present work. Type III-A kerogen proposed by Ungerer et al was employed to develop the inkbottle-shaped and slit nanopores with surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its phys i cal prop er ties, CO 2 is a per fect agent for stim u la tion of meth ane (CH 4 ) pro duc tion from ul tra-tight shale res er voirs, as well as from con ven tional res er voirs. Firstly, a higher CO 2 (than CH 4 ) ad sorp tion af fin ity to or ganic mat ter and clay min er als leads to CH 4 re place ment by CO 2 in or ganic matter and other min eral pore sur faces (Heller and Zoback, 2014;Zhou et al, 2019). This mech a nism pro duces an ac tive push of gas off the res er voir and en sures per ma nent bond ing of CO 2 in the shale vol ume.…”
Section: Introductionmentioning
confidence: 99%